Rancang Bangun Sistem Informasi Analisis Kepuasan dalam Proses Belajar Mengajar di SMA Negeri 3 Mataram Menggunakan MetodeQuality Function Deployment - Wahda Farah Batari; Budi Irmawati (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
A senior high school is responsible to deliver competitive human resources. A high school that has good facilities are more popular and attractive for junior high school students. To evaluate the school quality of service, we build a system to analyze the student's satisfaction with the learning process and services. To conduct the analysis, an information system was built to identify what components of the learning process needed to be improved. The method used is Quality Function Deployment (QFD) that clearly defines the needs and the expectations of students. The evaluation process was done by asking students to fill out a satisfaction questionnaire through the system. To get the analysis continuously this evaluation process can be carried out annually at the end of each school year. By using this computerized system, the evaluation results are obtained faster and more accurate.